The Effect of Islamic Character Education Factors on Green Entrepreneurial Behavior; A Case of State University Students in Banten Province - Ma'zumi, Ma'zumi; Syihabudin, Syihabudin; Najmudin, Najmudin (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to analyze the influence of Islamic Education factors on green entrepreneurial behavior, namely (1) the effect of social awareness on green entrepreneurial behavior, (2) the effect of cooperation on green entrepreneurial behavior, (3) the influence of innovation and creativity on green entrepreneurial behavior, (4) ) the influence of leadership on green entrepreneurial behavior, (5) the influence of work ethics on green entrepreneurial behavior. The population of this study were students of State Universities in Banten Province who had taken Islamic Religious Education Courses, with a sample of 232 students, which was obtained by multiplying the entire number of indicators as many as 29 with the number 8 referring to Ferdinand's opinion, The method used in this study is a descriptive quantitative data collected through a questionnaire and processed using Smart PLS software version 3.2.9. The results of this study indicate that (1) social awareness has a positive and significant effect on green entrepreneurial behavior, (2) cooperation has no positive and insignificant effect on green entrepreneurial behavior, (3) innovation and creativity have no positive and insignificant effect on green entrepreneurial behavior, (4) Leadership has no positive and significant effect on green entrepreneurial behavior, and (5) Work ethics has a positive and significant effect on green entrepreneurial behavior.